Development and evaluation of gum arabic-based antioxidant nanocomposite films incorporated with cellulose nanocrystals and fruit peel extracts. (December 2021) - Kang, Shufang; Xiao, Yaqing; Wang, Kunhua; Cui, Mengdi; Chen, Dan; Guan, Dong; Luan, Guangzhong; Xu, Huaide
Abstract: The active food packaging films prepared in this study used gum arabic (GA)-cellulose nanocrystals (CNC) as the film-forming matrix, and grape skin extract (GSE), pomegranate peel extract (PPE) and red pitaya peel extract (RPPE) as natural antioxidants by solution casting method. The combination of extracts changed the color and microstructure of the films, resulting in a decrease in mechanical strength and water resistance, but their flexibility and light transmittance were improved. Particularly, the PPE film can almost completely block the passage of ultraviolet light (200–400 nm). In addition, the composite films carrying the extracts possessed antioxidant capacity, which can extend the storage period of raspberries. The PPE film with the highest activity prominently reduced total color difference (4.08–2.08), weight loss rate (19.71–5.81%), moisture evaporation (21.29–18.22%) and fluctuation of nutrient content of the fruits in the raspberry preservation test. Graphical abstract: ga1 Highlights: Development of gum arabic/cellulose nanocrystals-biofilms added with peel extracts. Pomegranate peel extract (PPE) has the highest content of active compounds. The addition of extracts improved the flexibility and light resistance of films. The extracts effectively enhanced the antioxidant activities of composite films. PPE film showed the best effect on raspberry preservation.